BE_ZIVILSTRAF SK 2023 115 vom 12. Juli 2024 , Einstellung/Nichtanhandnahme - BE Obergericht (2024)
vorsätzliche Tötung, versuchte vorsätzliche Tötung, sexuelle Handlung mit Kindern, etc. | Strafgesetz